DESIGN AND ANALYSIS OF ATTACHMENT FOR ALUMINUM FOAM SANDWICH IN BLAST RESISTANT STRUCTURES - Akbar, Ilham
Increasing the safety of Armored Carrier (APC) is an important aspect of the threat of grenade or land mine. Vehicle resistance has implications for the level of safety when explosion occurs. In general, grenade or landmine was destroying the bottom of the vehicle. Then, the V shaped aluminum foam sandwich was developed as a protector for combat vehicle floor that is capable of managing explosive energy effectively. However, it is necessary to discuss critical components which are the determinants of the effectiveness of protector, that is the attachment structure. Therefore, this study discusses and analyzes the structural response when the structures is subjected blast load according to STANAG 4659 level 3. Numerical simulation is used with the Load Blast Enhanced (LBE) method in LS-DYNA. Three design concepts of attachment were obtained that were completed and carried out trade-offs, so that the most optimal design was choosen. The attachment used consists of bolts with a diameter of 20mm (M20) and a total of 14 pieces. The comparison parameter is the cross section force of the bolt- joint. Sandwich made of aluminum. Comparison of the response of the protector and the floor of the vehicle is a benchmark for obtaining an optimal design. Loading is defined as an explosion of 8 kg of TNT which is under the floor of a vehicle. From the results of simulations and analysis, a attachment design that has a configuration of tension bolt, c-beam, nut, and spring washer is obtained. The attachment is installed at the bottom of the vehicle floor. And the selected aluminum foam sandwich structure has a configuration that consists of aluminum foam that attaches to the floor and additional plates at the bottom.